Morocco : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Morocco. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation with Morocco discusses that gradually increasing growth, moderate inflation, and stronger external and fiscal buffers are expected over the medium term, benefiting from sustained reform implementation. However, this outlook remains subject to significant domestic and external risks: delays in implementing reforms, lower growth in key partner countries (particularly in the euro area), higher oil prices, geopolitical risks, and volatile financial conditions could weaken Morocco's resilience and economic prospects. Building on progress achieved in recent years, further fiscal and structural reforms are needed to consolidate gains in macroeconomic resilience and achieve higher and more inclusive growth. The discussions mainly focused on strengthening the resilience of the economy through continued fiscal reforms, greater exchange rate flexibility, and strengthened financial sector soundness. It also highlighted the need for pushing ahead with mutually-reinforcing and properly sequenced reforms to raise growth and inclusion, including by improving public sector governance, promoting private sector development, and reducing inequalities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet